The Assessment of the Type of Substrate and LEDs’ Irradiation Influence on Garden Cress Sprouts (Lepidium sativum L.) - Oana Livadariu; Carmen Maximilian; Anca Daniela Raiciu; Cristian-Paul Șerbănică (Applied Sciences, 2022)
In the current context of climate change and life on Earth, the purpose of this paper is to establish the effects of different light treatments (i.e., LEDs—white, blue, red, and sunlight) and two different substrates (i.e., gauze and biochar) on garden cress sprouts. In this respect, sprouts’ fresh weight and fresh length were statistically analyzed. In the case of the fresh weight, the results indicated that the most suitable substrate for better growth is biochar under all of the light treatments, with a 5.78% weight increase. On the other hand, the highest particular value regarding weight was obtained for gauze substrate under sunlight treatment, with a 4.08% weight increase compared to biochar substrate and sunlight treatment. Furthermore, red LED and biochar used as substrate improved the development of short radicles, with a decrease in length of 94.80% compared to gauze substrate and red LED treatment. The effect of LED irradiation was completed with biochemical analyses concerning polyphenols, flavonoid content, and antioxidant activity. Results suggest that blue LED is the most suitable source of artificial light to promote the accumulation of secondary metabolites, with a 9.88% higher concentration of flavonoids compared to the other light variants (2.22 ± 0.40 mg rutin equivalent/g fresh weight) and 37.98% higher concentration of polyphenols compared to the other light variants (2.76 ± 1.05 mg gallic acid equivalent/g fresh weight) in garden cress sprouts. The illumination with white LED produced the highest effect concerning antioxidant activity, with a 37.60% higher free radical scavenging activity.